2012
DOI: 10.1080/13607863.2012.702727
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of life satisfaction among older people in China: An examination of two cultural variables

Abstract: This article examines the relationships between the two cultural variables of having mianzi in social interactions and Chinese cultural beliefs of adversity and life satisfaction among older people in a coastal city in mainland China. The mediating effect of having mianzi in social interactions on the relationship between Chinese cultural beliefs of adversity and life satisfaction is also examined. The study applies a non-probability sampling and adopts a face-to-face interview approach using a questionnaire c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
1
7
1
Order By: Relevance
“…The finding was also consistent with previous research (Huang & Wu, 2012;Shek, 2005;Shek et al, 2003) and thus extended the literature on Chinese cultural beliefs of adversity to Chinese disaster survivors. Perhaps with the endorsement of positive Chinese cultural beliefs of adversity, the Wenchuan earthquake survivors became more likely to accept the adversities and believed they could overcome adversities in their lives.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The finding was also consistent with previous research (Huang & Wu, 2012;Shek, 2005;Shek et al, 2003) and thus extended the literature on Chinese cultural beliefs of adversity to Chinese disaster survivors. Perhaps with the endorsement of positive Chinese cultural beliefs of adversity, the Wenchuan earthquake survivors became more likely to accept the adversities and believed they could overcome adversities in their lives.…”
Section: Discussionsupporting
confidence: 90%
“…However, for the scale of Chinese cultural beliefs of adversity, the deletion of two negative cultural beliefs notably resulted in an increase in the Cronbach's alpha of the scale from 0.47 to 0.71 in this study, which was not observed in previous studies (Huang & Wu, 2012;Shek, 2005;Shek et al, 2003). The Wenchuan earthquake might have affected the negative beliefs of adversity among the survivors.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…It seems that through participating in recreational activity groups, disaster survivors not only overcome psychosocial problems themselves, but also promote personal resilience and growth by broadening and strengthening their social network, engaging in social activities and enhancing self-confidence. Previous research indicates that the availability of psychosocial resources, such as social network, social support, social engagement and positive beliefs about adversity may counteract or moderate the potentially disruptive influence of adversity (Cleary & Houts 1984, Glass et al 1999, Brewin et al 2000, Yip et al 2007, Phillips 2009, Ke et al 2010, Huang & Wu 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research on QOL for the Chinese older people is mainly associated with variables such as family support, financial restraint, cultural beliefs, gender and geographic locations of living (urban, rural) (e.g., Huang and Wu, ). Research found that older parents who live in three generational households or with grandchildren had better psychological well‐being than those living alone (Silverstein et al ., ).…”
Section: Literature Reviewmentioning
confidence: 99%